2000
DOI: 10.3109/07853890008998823
|View full text |Cite
|
Sign up to set email alerts
|

Non-lipid-related effects of statins

Abstract: The beneficial effects of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) on coronary events have generally been attributed to their hypocholesterolaemic properties. However, as mevalonate and other intermediates of cholesterol synthesis (isoprenoids) are necessary for cell proliferation and other important cell functions, effects other than cholesterol reduction may explain the pharmacological properties of statins. In the present review, we discuss the current knowledge on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
218
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(230 citation statements)
references
References 138 publications
7
218
1
4
Order By: Relevance
“…It has been reported that TNF-α expression is significantly higher in the blood of patients with rheumatoid arthritis (22). Furthermore, multiple inflammatory factors including TNF-α, IL-1β and IL-6 stimulate the differentiation and formation of osteoclasts (23)(24)(25)(26). Therefore, the current study investigated whether TNF-α, IL-1β and IL-6 levels differed between healthy children and those with ankle fracture.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that TNF-α expression is significantly higher in the blood of patients with rheumatoid arthritis (22). Furthermore, multiple inflammatory factors including TNF-α, IL-1β and IL-6 stimulate the differentiation and formation of osteoclasts (23)(24)(25)(26). Therefore, the current study investigated whether TNF-α, IL-1β and IL-6 levels differed between healthy children and those with ankle fracture.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies show that statins have many additional cardiovascular protective effects beyond the ability to lower serum cholesterol levels [10]. Anti-oxidant action is one of the pleiotropic effects of statins [11,12]. We and other previously reported that statins enhanced the PON1 gene promoter activity in a human hepatocellular carcinoma cell line, HepG2 cells [13], or increased the serum PON1 concentrations and activities in patients with hypercholesterolemia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-oxidation 5 has been suggested as one of the pleiotropic effects of statins [11]. Also, simvastatin has been reported to inhibit macrophage-dependent LDL oxidization [12], and atorvastatin to inhibit copper-derived LDL oxidization [13].…”
Section: Introductionmentioning
confidence: 99%